EXPLORING THE INDONESIAN ECONOMIC LANDSCAPE AND STRUCTURAL CHANGE - Firdaus, Muhammad; Kurniawan, Budi; Mulatsih, Sri (Journal of Indonesian Economy and Business, 2012)
In assessing the economic impact of a sector or a group of sectors on a single orÂ multiregional economy, input-output analysis has been proven to be a popular method.This paper explores the degree of structural change of the Indonesian economy using theÂ input-output frame work. It examines how linkages among economic sectors have evolvedÂ from 1971-2008 and identifies which economic sectors exhibited the highest inter-sectoralÂ linkages. The study finds that manufacturing consistently becomes the key sector in theÂ Indonesian economy. Indonesian cannot afford to leapfrog the industrialization stage andÂ largely depend on a service-oriented economy when the potential for growth still liesÂ primarily in manufacturing. The graphical presentation of inter-industry relationshipÂ through the âMultiplier Product Matrixâ (MPM) and its associated âeconomicÂ landscapeâ provides a visualization of the Indonesian economic landscape for selectedÂ years and how it has changed over time.Keywords: economic landscape, structural change, input output model, key sector